2016
DOI: 10.1038/ncomms13016
|View full text |Cite
|
Sign up to set email alerts
|

ANGPTL2 activity in cardiac pathologies accelerates heart failure by perturbing cardiac function and energy metabolism

Abstract: A cardioprotective response that alters ventricular contractility or promotes cardiomyocyte enlargement occurs with increased workload in conditions such as hypertension. When that response is excessive, pathological cardiac remodelling occurs, which can progress to heart failure, a leading cause of death worldwide. Mechanisms underlying this response are not fully understood. Here, we report that expression of angiopoietin-like protein 2 (ANGPTL2) increases in pathologically-remodeled hearts of mice and human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
74
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(78 citation statements)
references
References 71 publications
(91 reference statements)
3
74
1
Order By: Relevance
“…Furthermore, in mice, circulating ANGPTL2 concentrations increase as HF induced by transverse aorta constriction develops, related primarily to increases in heart-secreted ANGPTL2. 21 Circulating ANGPTL2 concentrations also inversely correlate with the percent of fractional shortening in mice. In mouse models of HF, inhibition of ANGPTL2 secretion by injection of AAV6-shANGPTL2 antagonizes cardiac dysfunction, 21 suggesting that cardiomyocytes are a major source of secreted ANGPTL2 in HF conditions.…”
Section: A Novel Function For Angptl2 In Hfmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, in mice, circulating ANGPTL2 concentrations increase as HF induced by transverse aorta constriction develops, related primarily to increases in heart-secreted ANGPTL2. 21 Circulating ANGPTL2 concentrations also inversely correlate with the percent of fractional shortening in mice. In mouse models of HF, inhibition of ANGPTL2 secretion by injection of AAV6-shANGPTL2 antagonizes cardiac dysfunction, 21 suggesting that cardiomyocytes are a major source of secreted ANGPTL2 in HF conditions.…”
Section: A Novel Function For Angptl2 In Hfmentioning
confidence: 99%
“…Further investigation is required to determine whether increased circulating ANGPTL2 concentrations could serve as a found that increased ANGPTL2 activity induced in the pathologically stressed heart accelerated cardiac dysfunction by inactivating both AKT and sarco(endo)plasmic reticulum Ca 2+ -ATPase (SERCA)2a signaling and by decreasing myocardial energy metabolism in an autocrine/paracrine manner ( Figure 5). 21 Conversely, ANGPTL2 suppression restored cardiac function and myocardial energy metabolism, blocking pathologic remodeling. 21 It is noteworthy that this suppressive activity of ANGPTL2 on cardiac function is not attributable to its pro-inflammatory effect.…”
Section: Angptl2 Expression Is Associated With Cellular Senescencementioning
confidence: 99%
See 2 more Smart Citations
“…Recently, we reported that ANGPTL2 secreted from pathologically stressed heart accelerates cardiac dysfunction, and that suppression of ANGPTL2 production from the heart restored cardiac function and myocardial energy metabolism, thereby blocking HF development. 11, 20 In that study, although we observed increased levels of circulating ANGPTL2 in mice with cardiac dysfunction, we did not address whether ANGPTL2 affects cardiomyocytes in an endocrine or autocrine/paracrine manner. Interestingly, another study reported that circulating ANGPTL2 levels are higher in HF patients than in controls, and that cardiac function is inversely correlated with levels of ANGPTL2 circulating in the periphery, 21 although this study did not address underlying mechanisms.…”
Section: Human Studiesmentioning
confidence: 87%